Presentation, diagnosis, and management of popliteal artery entrapment syndrome: 11 years of experience with 61 legs. (13th June 2017) - Corneloup, L.; Labanère, C.; Chevalier, L.; Jaussaud, J.; Mignot, A.; Gencel, L.; Corneloup, O.; Midy, D.
Abstract : Popliteal artery entrapment syndrome (PAES) is still underdiagnosed yet it may significantly interfere with lifestyle, especially among young sportspeople, with symptoms like intermittent claudication. Although case reports and small case series are sometimes published, studies with larger populations are quite rare. This study summarizes our experience with PAES on 61 limbs (35 patients) over a period of 11 years, describing the demographics, the disease, and the diagnostic and therapeutic methods used with PAES patients. In a population of 327 consecutive explored symptomatic sportspersons, PAES was confirmed in 35 patients on 61 pathologic limbs. The median time with the symptoms before diagnosis was 34 months (range, 3‐180 months). The mean age of patients was 30.5 years (range, 17‐52 years) with 83% of males. The proportion of patients diagnosed with bilateral PAES was 74%. The main sports practiced were running (15 patients, 43%), soccer (nine patients, 26%), rugby (two patients), and athletics (two patients). Among 21 patients, intra‐compartmental pressure measurements (ICP) found 18 (86%) to have an associated chronic exertional compartment syndrome (CECS). Among the patients followed up after PAES surgery, 80% were able to resume sport at a level comparable to that before the onset of pain. PAES could be sought earlier in young sportspeople who experience unexplained leg pain during exercise to diagnose the disease and avoid complications in a timely manner. Compartmental pressures should systematically be measured in the search for an associated CECS.